Ulumul Qur’an dalam Konteks Pendidikan - Epik Teyebu; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The Qur'an as a beacon of life for Muslims has holiness, authenticity and breadth of discussion that never dries up, in fact it cannot be refuted in line with advances in science and technology. The existence of the Al-Qur'an revealed by Allah as a revelation to the Prophet Muhammad SAW in the form of a mushaf has very interesting and complex dynamics to be studied and practiced as a guide to mankind. The word tarbiyah is used for a broader meaning, namely the process of coaching and direction for the formation of personality and mental attitudes, while the word taklim is used for a more specific meaning, namely the process of providing provisions in the form of knowledge and skills and ta'dib is the material taught including language lessons, speech lessons. , good writing lessons, history lessons about heroes and great commanders in order to absorb the experience of their success, swimming, archery and horse riding (skills lessons). Based on the terms above, education according to the Qur'an is formulated as an effort carried out in a planned and gradual manner to provide knowledge, skills and mental attitudes to students as provisions for carrying out their duties as servants and caliphs of Allah on earth. Based on the terms above, education according to the Qur'an is formulated as an effort carried out in a planned and gradual manner to provide knowledge, skills and mental attitudes to students as provisions for carrying out their duties as servants and caliphs of Allah on earth. The aim of education according to the Qur'an is to develop humans so that they are able to carry out their functions as servants of Allah and His caliphs in order to build this world in accordance with the concepts set by Allah or in other words to make humans devoted to Allah SWT.